2021
DOI: 10.3389/fphar.2021.671498
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Herbal Medicines, Bioactive Metabolites, and Plant Products Against COVID-19: Update on Clinical Trials and Mechanism of Actions

Abstract: SARS-CoV-2 is the latest worldwide pandemic declared by the World Health Organization and there is no established anti-COVID-19 drug to combat this notorious situation except some recently approved vaccines. By affecting the global public health sector, this viral infection has created a disastrous situation associated with high morbidity and mortality rates along with remarkable cases of hospitalization because of its tendency to be high infective. These challenges forced researchers and leading pharmaceutica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 74 publications
0
70
1
Order By: Relevance
“…The ingredients of LHQW recipes, including quercetin, kaempferol, and luteolin, can target ACE2 and 3CLpro to affect viral replication and maturation [21]. At the same time, LHQW reduced systemic and airway in ammation by regulation of the inherent and acquired immune systems through the decrease of IL-6 levels to relieve COVID-19 symptoms [21]. However, in the present study, we failed to show that LHQW alone accelerated nucleic acid negative conversion time.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…The ingredients of LHQW recipes, including quercetin, kaempferol, and luteolin, can target ACE2 and 3CLpro to affect viral replication and maturation [21]. At the same time, LHQW reduced systemic and airway in ammation by regulation of the inherent and acquired immune systems through the decrease of IL-6 levels to relieve COVID-19 symptoms [21]. However, in the present study, we failed to show that LHQW alone accelerated nucleic acid negative conversion time.…”
Section: Discussioncontrasting
confidence: 70%
“…3CLpro is a main viral proteinase, which controls the activities of the coronavirus replication complex [20]. The ingredients of LHQW recipes, including quercetin, kaempferol, and luteolin, can target ACE2 and 3CLpro to affect viral replication and maturation [21]. At the same time, LHQW reduced systemic and airway in ammation by regulation of the inherent and acquired immune systems through the decrease of IL-6 levels to relieve COVID-19 symptoms [21].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the fact that numerous drugs do exist that have clinically proven antiviral properties (Indari et al, 2021) and several drugs that show a limited potential to alleviate COVID-19 symptoms (Lam et al, 2020;Raju et al, 2021), none of them have proven to work efficiently to reduce COVID-19 associated mortality. Nevertheless, several in vitro studies have demonstrated the potential of several phytochemicals to inhibit COVID-19 infectious cycle in humans at various stages (Alam et al, 2021;Behl et al, 2021;Marmitt et al, 2021;Merarchi et al, 2021). These phytochemicals have been demonstrated to inhibit viral entry, viral replication, or viral release -in addition to attenuating the host pathological responses (Figure 2).…”
Section: Covid-19 Virus and Its Life Cyclementioning
confidence: 99%
“…Natural products provide a source of bioactive molecules that can be exploited for novel and effective treatments to prevent the fatal evolution of this disease. 2 , 3 , 4 , 5 , 6 These natural biomolecules could interfere at any stage of the virus life cycle, from entering the cell to its replication, assembly, and exit from the cell, as well as by triggering virus clearance. 3 , 7 , 8 , 9 , 10 Autophagy, a vesicular-driven degradation pathway of cellular components, is triggered as a cellular stress response to viral infection, and it is involved in all steps of CoV replication and propagation.…”
Section: Introductionmentioning
confidence: 99%